2008
DOI: 10.1103/physrevb.78.165410
|View full text |Cite
|
Sign up to set email alerts
|

Structural distortions in 5–10 nm silver nanoparticles under high pressure

Abstract: We present experimental evidence that silver nanoparticles in the size range of 5 -10 nm undergo a reversible structural transformation under hydrostatic pressures up to 10 GPa. We have used xray diffraction with a synchrotron light source to investigate pressure-dependent and size-dependent trends in the crystal structure of silver nanoparticles in a hydrostatic medium compressed in a diamond-anvil cell. Results suggest a reversible linear pressure-dependent rhombohedral distortion which has not been previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
2
37
0
1
Order By: Relevance
“…Mechanical property. As discussed here and in previous work [12][13][14][15][16]18 , high-pressure stress can effectively induce Ag microstructure phase transformations and potentially manipulate the mechanical stability of Ag nanoparticles. Gu et al 12 found an unexpected high stiffness of Ag and gold (Au) nanoparticles under high pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical property. As discussed here and in previous work [12][13][14][15][16]18 , high-pressure stress can effectively induce Ag microstructure phase transformations and potentially manipulate the mechanical stability of Ag nanoparticles. Gu et al 12 found an unexpected high stiffness of Ag and gold (Au) nanoparticles under high pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Many chemical methods use such defect structures (also the most reactive sites) to achieve oriented growth of Ag nanostructures; for example, oriented attachment was used to grow chain-like Ag nanostructures 11 . It has been shown elsewhere that an external stress induced by high-pressure compression can alter the mechanism of defect motion in atomic lattices through induced phase transformations [12][13][14] . Depending on the pressure condition, different Ag phase and structural transformations were observed: under hydrostatic pressure up to 10 GPa, Ag nanoparticles with sizes of 5-10 nm underwent a reversible, linear, pressure-dependent structural transformation 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We are unable to propose a mechanism similar to that proposed in Ref. 99. This also doesn't necessarily mean that the variation of γ is how the crystal is distorting because of the uniqueness problem wherein there are several solutions for possible distortion here but this is an appropriate way of quantifying this distortion from an fcc to orthorhombic structure.…”
Section: Proposed Distortion Mechanismmentioning
confidence: 80%
“…99 The particular problem of the distortion of icosahedral structure is both non-linear and constrained.…”
Section: Proposed Distortion Mechanismmentioning
confidence: 99%